1920 Diary - Babelʹ, I. (Isaak), 1894-1940.; Avins, Carol; Willetts, H. T. (New Haven : Yale University Press, 1995)
The Russian writer Isaac Babel (1894-1940) is widely acknowledged to be one of the great masters of twentieth-century literature, hailed as a genius by such critics as Lionel Trilling and Irving Howe. The work for which he is best known is a cycle of stories called Red Cavalry, which depicts the exploits of the Cossack cavalry during the Polish-Soviet war of 1919-1920 and is based on Babel's experiences as he rode with the Cossacks during the campaign. Babel kept a diary during this period, in which he recorded the devastation of the war, the extreme cruelty of the Polish and Red armies alike toward the Jewish population in the Ukraine and eastern Poland, and his own conflicted role as both Soviet revolutionary and Jew. The 1920 Diary, a vital source for Red Cavalry as well as a compelling narrative, is now published in English for the first time. The 1920 Diary is the most significant contemporary account of the tragedy of Eastern European Jewry during this period. The Diary also yields important insights into Babel's personal evolution, showing his youthful curiosity and his anguish as, frequently concealing his own Jewish identity, he mingled with the victimized Jews of the region's shtetls and with his Cossack comrades. Finally, the Diary sheds light on Babel's artistic development, revealing the path from observations recorded in excitement and despair to the painstakingly crafted narratives of the Red Cavalry cycle.
Frontmatter -- Contents -- List of Illustrations -- Editor's Acknowledgments -- Editor's Note on the Translation -- Map of Poland in the Era of the Polish-Soviet War -- Map of Babel's Route with the First Cavalry Army -- Introduction: Isaac Babel's "Red Cavalry" Diary -- 1920 Diary -- Appendix: Babel's Publications in the Red Cavalryman -- Notes to Babel's Texts.
Translated from Russian.
Includes bibliographical references (pages 109-126).
Print version record.
In English.
eBooks on EBSCOhost
Keywords: Babelʹ, I. -- 1894-1940 -- Diaries; Babelʹ, I. -- 1894-1940; Soviet Union -- History -- Revolution, 1917-1921 -- Personal narratives, Russian; Soviet Union -- History -- Revolution, 1917-1921 -- Campaigns; Authors, Russian -- 20th century -- Diaries; Soldiers -- Soviet Union -- Diaries; URSS -- Histoire -- 1917-1921 (Révolution) -- Campagnes et batailles; Écrivains russes -- 20e siècle -- Journaux intimes; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY; BIOGRAPHY & AUTOBIOGRAPHY -- Literary; Authors, Russian; Military campaigns; Soldiers; Soviet Union; Regions & Countries - Europe; History & Archaeology; Russia & Former Soviet Republics; 1900-1999; History; Diaries; Personal narratives -- Russian